TREND OF SHARIA BANKING FINANCIAL PERFORMANCE IN THE PANDEMIC TIME COVID 19 - Riyan Pradesyah; Santiyana Putri (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study was to determine the level of financial performance and the level of profitability ratios of Islamic people's finance banks using the ratio of Return On Asset (ROA) and Return On Equity (ROE). The ROA ratio is calculated by comparing net income to the company's total assets. Meanwhile, ROE is calculated by comparing net income to the company's total equity. The research method used is quantitative method.              The results showed that in terms of profitability, the financial ratio Return on Assets (ROA) with the lowest ROA prediction in 2021 is 2.21%. And the trend of forecasting the performance of Islamic banking in 2019-2021 in terms of profitability, the Financial Ratio Return on Equity (ROE) is also predicted to decline in 2020 but in 2021 the financial ratio ROE is reduced to be able to rise again with a better ROE than 2020, which is 21 , 15%. Keywords: Trend Analysis, Financial Performance, ROA, ROE